Stroke as a Potential Complication of COVID-19-Associated Coagulopathy: A Narrative and Systematic Review of the Literature - Szegedi, István (J Clin Med, 2020)
Coronavirus disease 2019 (COVID-19) is the most overwhelming medical threat of the past few decades. The infection, caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), can cause serious illness leading to respiratory insufficiency, and, in severely ill patients, it can progress to multiple organ failure leading to death. It has been noted from the earliest reports that the disease influences the hemostasis system and a hallmark of severe infection is elevated D-dimer levels. The profound coagulation changes in COVID-19 seem to be linked to inflammation-related events and severe endothelial cell injury. Besides the high incidence of venous thromboembolic events in SARS-CoV-2 infections, arterial events, including cerebrovascular events, were found to be associated with the disease. In this review, we aimed to summarize the available literature on COVID-19-associated coagulopathy and thrombosis. Furthermore, we performed a systematic search of the literature to identify the characteristics of stroke in COVID-19. Our findings showed that acute ischemic stroke (AIS) is the most frequent type of stroke occurring in infected patients. In most cases, stroke was severe (median NIHSS:16) and most of the patients had one or more vascular risk factors. Laboratory findings in AIS patients were consistent with COVID-19-associated coagulopathy, and elevated D-dimer levels were the most common finding. The outcome was unfavorable in most cases, as a large proportion of the reported patients died or remained bedridden. Limited data are available as yet on outcomes after acute vascular interventions in COVID-19 patients. In the future, well-designed studies are needed to better understand the risk of stroke in COVID-19, to optimize treatment, and to improve stroke care.